Spiritual Well-Being of Islamic Boarding School Students: A Comparative Study of Practitioners and Non-Practitioners of the Naqshbandiyya Khalidiyya order - Ilyas, Ahmad Jalaludin; Ariyati, Ika; Hendar, Kus (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study was designed to analyze differences in spiritual well-being as an indicator of inner peace between students who practice and those who do not practice the Naqshbandiyya Khalidiyya order at the Baitul Mustaqim Islamic Boarding School, Central Lampung. Using a quantitative comparative non-experimental method, a total of 108 students were selected through purposive sampling, consisting of 55 practicing students and 53 non-practicing students. The Spiritual Well-Being Scale (SWBS) was used to measure the dimensions of religious and existential well-being, while the data analysis technique employed an independent sample t-test. The results showed that the average spiritual well-being score of practicing students (Mean = 87.49; SD = 11.17) was descriptively higher than that of non-practicing students (Mean = 86.25; SD = 9.663). However, the independent sample t-test yielded a significance value of 0.536 (p > 0.05), indicating no significant difference between the two groups. The implications of this study suggest that Thoriqoh practices alone are insufficient to improve spiritual well-being, and that a holistic approach considering social support and existential aspects should be incorporated into guidance and counseling services in Islamic boarding schools.